Quizlet And Vocabulary Mastery: Students’ Perception - Ayumi Pratiwy Tanjung; Sholihatul Hamidah Daulay (English Language and Literature International Conference (ELLiC) Proceedings, 2022)
This study determined students' perception of the use of quizlet application in students' vocabulary mastery. Quizlet is a suitable smartphone-based learning used for learners at various levels of education and at various levels disciplines, not only limited to vocabulary learning. It described the students' perception of the use of quizlet application on the vocabulary of students at Junior High Schools in Bandar Huluan, totaling 20 students. This study used a qualitative descriptive research method in which this research described something as it is by using words, such as observation and interviews to 20 students. The results indicated that quizlet has several benefits in the process of teaching English, especially vocabulary. From the students’ perception, it can be concluded that 15 students said that learning vocabulary by using the quizlet application was very comfortable, interesting and easy to understand. On the other hand, 5 students said that learning vocabulary by using the quizlet application was a little difficult to understand. There are several factors why this can happen, including obstacles in operating the quizlet application such as the lack of student knowledge about how to use the features of the quizlet application, and also the lack of internet network access on their smartphones.